2017
DOI: 10.1016/j.jcis.2017.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Surface complexation modeling of calcite zeta potential measurements in brines with mixed potential determining ions (Ca2+, CO32−, Mg2+, SO42−) for characterizing carbonate wettability

Abstract: This study presents experiment and surface complexation modeling (SCM) of synthetic calcite zeta potential in brine with mixed potential determining ions (PDI) under various CO partial pressures. Such SCM, based on systematic zeta potential measurement in mixed brines (Mg, SO, Ca and CO), is currently not available in the literature and is expected to facilitate understanding of the role of electrostatic forces in calcite wettability alteration. We first use a double layer SCM to model experimental zeta potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 37 publications
6
98
0
Order By: Relevance
“…Calcium Ca 2+ and carbonate CO 2− 3 are known as potential determining ions of calcite [9]. Calcite surface sites are predominantly in their hydrated forms >CaOH −(1−x) and >CO 3 H +(1−x) with x ≈ 0.25 [8,40]. Potential determining ions form complexes with these surface sites, and thereby modify the overall surface charge and potential.…”
Section: Zeta Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium Ca 2+ and carbonate CO 2− 3 are known as potential determining ions of calcite [9]. Calcite surface sites are predominantly in their hydrated forms >CaOH −(1−x) and >CO 3 H +(1−x) with x ≈ 0.25 [8,40]. Potential determining ions form complexes with these surface sites, and thereby modify the overall surface charge and potential.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…The corresponding concentrations are presented in Table 2. For pure calcite, the main anion is HCO − 3 , which complexes onto calcite (although more weakly than carbonate CO 2− 3 [8,40]) and thereby makes ζ decrease. In all the solutions containing calcium hydroxide, the main anion is no more bicarbonate but hydroxide, which is not a potential determining ion, and therefore does not affect the ζ potential.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…The SCM results were qualitatively validated with different carbonate/brine zeta-potential measurements. Song et al [25] applied SCM and reported quantitative agreement with experimental zeta-potential measurements of synthetic calcite and multiple brine recipes. The SCM surface reactions are based on the model proposed in [26], which includes different SCM reactions compared to the models in [21,24].…”
Section: Surface Complexation Modelmentioning
confidence: 81%
“…For calcite/brine/crude-oil system, the adsorption of ions on crude-oil/brine and calcite/brine interfaces determine the surface charges and the corresponding zeta-potentials. The SCM has been employed to gain insight on the effect of electrokinetics on wettability in the context of brine chemistry in carbonates [20,21,24,25]. Brady et al [21] used SCM based on surface reactions proposed in [22,23] to predict zeta-potentials for both rock/brine and brine/crude-oil interfaces in sandstone and carbonate rocks.…”
Section: Surface Complexation Modelmentioning
confidence: 99%
See 1 more Smart Citation